Working with a troubled 7-year old in a primary school – lessons learnt by a learning support assistant from Work Discussion seminars. Issue 3 (1st September 2020) - Pike, Bernice
ABSTRACT: The author describes her work as a learning support assistant, and the changes and developments in her thinking and her approach to work in class with an overactive, excitable boy who could not tolerate making mistakes and often refused to try the tasks he was set in class. The Work Discussion seminar the author attended as part of her Psychoanalytic Observational Studies course provided her with a different way of understanding and thinking about the boy and of working with him, which led to small, positive changes. The paper focuses on the work of one academic year.